Communications and the Future—Part I: Introduction (Washington University Law Quarterly, 1967)
Communications’ increasing importance in our daily lives requires that the law assume an increased duty in the supervision and regulation of media operation. For this reason, the Washington University Law Quarterly presents this two part symposium on communications in general, and television in particular. As satellites are placed in orbit and begin transmitting, as cable television reaches more and more homes, and as new tax and other economic incentives are sought to encourage creative programming, lawyers will have to focus on the various problems and possibilities so that the legal response to these developments will be a proper and adequate one. These Articles seek to prepare the profession by presenting “non-legal” materials on the structure and economics of the television industry, the technology of communications, new proposals for FCC regulation, and the future evolution of the industry, including proposals for cable television, pay television, and the use of satellites, waveguides, laser pipes, and computer link-ups for transmission and programming.
Keywords: Radio and television